2010
DOI: 10.1088/0067-0049/192/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Supernova Constraints and Systematic Uncertainties From the First Three Years of the Supernova Legacy Survey

Abstract: We combine high redshift Type Ia supernovae from the first 3 years of the Supernova Legacy Survey (SNLS) with other supernova (SN) samples, primarily at lower redshifts, to form a high-quality joint sample of 472 SNe (123 low-z, 93 SDSS, 242 SNLS, and 14 Hubble Space Telescope). SN data alone require cosmic acceleration at > 99.999% confidence, including systematic effects. For the dark energy equation of state parameter (assumed constant out to at least z = 1.4) in a flat universe, we find w = −0.91 +0.16 −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
872
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 781 publications
(906 citation statements)
references
References 103 publications
28
872
2
4
Order By: Relevance
“…Prominent examples include the supernova and weak lensing programs of the CFHT Legacy Survey (CFHTLS; Conley et al 2011;Semboloni et al 2006a;Heymans et al 2012b), the ESSENCE supernova survey (Wood-Vasey et al, 2007), BAO measurements from the Sloan Digital Sky Survey (SDSS; Eisenstein et al 2005;Percival et al 2010;Padmanabhan et al 2012), and the SDSS-II supernova survey . These have been complemented by extensive multi-wavelength studies of local and high-redshift supernovae such as the Carnegie Supernova Project (Hamuy et al, 2006;Freedman et al, 2009), by systematic searches for z > 1 supernovae with Hubble Space Telescope Suzuki et al, 2012), by dark energy constraints from the evolution of X-ray or optically selected clusters (Henry et al, 2009;Vikhlinin et al, 2009;Rozo et al, 2010), by improved measurements of the Hubble constant (Riess et al, , 2011Freedman et al, 2012), and by CMB data from the WMAP satellite (Bennett et al, 2003;Larson et al, 2011) and from ground-based experiments that probe smaller angular scales.…”
Section: Looking Forwardmentioning
confidence: 99%
See 4 more Smart Citations
“…Prominent examples include the supernova and weak lensing programs of the CFHT Legacy Survey (CFHTLS; Conley et al 2011;Semboloni et al 2006a;Heymans et al 2012b), the ESSENCE supernova survey (Wood-Vasey et al, 2007), BAO measurements from the Sloan Digital Sky Survey (SDSS; Eisenstein et al 2005;Percival et al 2010;Padmanabhan et al 2012), and the SDSS-II supernova survey . These have been complemented by extensive multi-wavelength studies of local and high-redshift supernovae such as the Carnegie Supernova Project (Hamuy et al, 2006;Freedman et al, 2009), by systematic searches for z > 1 supernovae with Hubble Space Telescope Suzuki et al, 2012), by dark energy constraints from the evolution of X-ray or optically selected clusters (Henry et al, 2009;Vikhlinin et al, 2009;Rozo et al, 2010), by improved measurements of the Hubble constant (Riess et al, , 2011Freedman et al, 2012), and by CMB data from the WMAP satellite (Bennett et al, 2003;Larson et al, 2011) and from ground-based experiments that probe smaller angular scales.…”
Section: Looking Forwardmentioning
confidence: 99%
“…The largest high-redshift (z ≈ 0.4 − 1.0) data sets are those from the ESSENCE survey (Wood-Vasey et al 2007; Narayan et al, in prep. ; ∼200 spectroscopically confirmed Type Ia SNe) and the CFHT Supernova Legacy Survey (SNLS; Astier et al 2006;Conley et al 2011;Sullivan et al 2011; ∼500 spectroscopically confirmed Type Ia SNe in the three-year data set SNLS3). At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction.…”
Section: The Current State Of Playmentioning
confidence: 99%
See 3 more Smart Citations